A Tutorial on Moving Target Defense Approaches Within Automotive Cyber-Physical Systems - Potteiger, Bradley; Zhang, Zhenkai; Cheng, Long; Koutsoukos, Xenofon (Frontiers in Future Transportation, 2022)
Moving Target Defenses (MTD) have become a popular and emerging defense strategy for the protection of traditional information technology systems. By their very nature, MTD strategies are designed to protect against adversary reconnaissance efforts on static platforms, essentially sitting back and having unlimited time to identify, craft, execute, and scale an exploit. With the rapid adoption of distributed automotive Cyber-Physical Systems (CPS) ranging from self driving cars, to connected transportation infrastructure, it is becoming more apparent that third party supply chains, increased remote communication interfaces, and legacy software stacks are making the traditionally designed standalone systems become more susceptible to safety-critical cyber-attacks. MTD strategies within the automotive CPS domain have to delicately balance the tradeoff between security and real time predictability, maintaining the safety constraints of the systems. In this paper, we explore the various MTD strategies presented within the literature while discussing potential applicability and strategies sufficient for the automotive CPS domain.